"And after the fire a soft murmuring sound ..." The Abiding Significance of Judaism for Christian Identity - Rutishauser, Christian M. (Studies in Christian-Jewish Relations, 2011)
Since the Second World War the pioneer phase of Jewish-Christian dialogue has achieved a relatively trusting relationship between both parties and major theological issues have been reflected on and dealt with. With the retirement of this generation of pioneers, while also reviewing history under the influence of the shock of the Shoah, we have to consider a change of paradigm at this time. First of all, a wider public should be involved in the dialogue in the hope of learning to fundamentally construct identity through dialogue. Learnings from the various phases of all of history should be kept in mind. Assuming an active relationship not only with Islam but also with any other interreligious dialogue is of paramount importance in a global world. On the concrete level, a redefinition of monotheism is needed in response to the associations being made between monotheism and violence. Further, the history of salvation has to be re-defined so that not only Jews and Christians are perceived as being in a generative relationship as “people of God” but so that the whole history of the world is perceived in a similar theological manner. A spirituality of action and an understanding of identity as co-constituted by the Other are valuable contributions of the Jewish-Christian dialogue to world culture.